Surgical wound immunotherapy: an immunotherapeutic nanoparticle spray may improve post-surgery tumour control - Liebers, Reinhard; Jäger, Dirk (Nature nanotechnology, 2019)
An immunotherapeutic nanoparticle spray may improve post-surgery tumour control.